EVALUATION OF ARABIC LANGUAGE LEARNING AT MADRASAH TSANAWIYAH ALI IMRON BANDAR SELAMAT SCHOOL TEMBUNG-NORTH SUMATRA - Nurhayati, Nurhayati; Usiono, Usiono (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
Learning Arabic in middle school plays an important role in forming students' communication skills and understanding culture and religion. However, there are concerns about the extent to which students understand the materials being taught. This research aims to assess students' understanding of learning Arabic at Al-Tsanawiyah Ali Imron School and to identify the factors that affect this understanding. This research uses a qualitative approach with survey and interview methods. Data were collected through questionnaires distributed to students and interviews with the Arabic language teacher at Al-Tsanawiya Ali Amron School. Data analysis was conducted using descriptive techniques to describe students' understanding. The results of the research showed that the majority of students have a good understanding of the basics of the Arabic language, but there are difficulties in the aspects of grammar and vocabulary. Factors affecting students' understanding include teaching methods, students' interests, and parental support. Although students' basic understanding of Arabic is very good, there is a need to improve teaching methods and increase student motivation. Recommendations for curriculum development and training of Arabic language teachers at Al-Tsanawiya Ali Amron High School are also proposed.